Community health volunteers' contribution to tuberculosis patients notified to National Tuberculosis program through contact investigation in Kenya - Abongo, Tabitha; Ulo, Benson; Karanja, Sarah (CrossMark, 2020)
Background: Contact investigation is important in finding contacts of people who have Tuberculosis (TB) disease so that they can be given treatment and stop further transmission. The main objective of this study was to assess the contribution of community health volunteers (CHVs) to the number of TB patients notified to the National program in Kenya through household contact screening and referral of persons with TB signs and symptoms to the facilities for further investigation. Methods: This was a retrospective desk review of project reports submitted to Amref Health Africa in Kenya by the sub-recipients implementing activities in the 33 counties with Case Notification Rate (CNR) of less 175/100,000 and Treatment Success Rate (TRS) of less than 88% as per the National strategic plan 2015-2018. Data for this study covered a period between January and December 2016. Data on the notified TB patients was obtained from the National Tuberculosis Information Basic Unit (TIBU). The study population included all the TB index cases whose households were visited by CHVs for contact screening. Data was recorded into excel spreadsheets where the descriptive analysis was done, proportions calculated and summarized in a table. Results: Community health volunteers visited a total of 26,307 TB patients (index cases) in their households for contact screening. A total of 44,617 household members were screened for TB with 43,012 (96.40%) from households of bacteriologically confirmed TB patients and 1606 (3.60%) from households of children under 5 years. The proportion of the persons referred to the number screened was 19.6% for those over 5 years and 21.9% from under 5 years with almost the same percentages for males and females at 19.2% and 19.7% respectively. The percentage of (TB) cases identified through tracing of contacts in these counties improved to 10% (5456) of the 54,913 cases notified to the National TB Program. Conclusions: This study showed that in the 33 counties of Global Fund TB project implementation, the percentage of TB cases identified through tracing of contacts improved from 6 to 10% while the percentage of notified TB cases; all forms contributed through community referrals improved from 4 to 8%. Community health volunteers can play an effective role in household contact screening and referrals for the identification of TB.
© The Author(s). 2020 Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article's Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article's Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/. The Creative Commons Public Domain Dedication waiver (http://creativecommons.org/publicdomain/zero/1.0/) applies to the data made available in this article, unless otherwise stated in a credit line to the data.
Keywords: Community health volunteers; Community health workers; Contact screening; Contact tracing; Tuberculosis